Epidemiological, serological and molecular aspects of hepatitis B and C in children and teenagers of municipal daycare facilities schools and schools in the city of Santos - Maria Célia Cunha Ciaccia; Regina Célia Moreira; Marcílio Figueiredo Lemos; Isabel Takano Oba; Gilda Porta (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Objective: To estimate the prevalence of the serological markers anti-HBc, HBsAg and anti-HBs of hepatitis B and anti-HCV of hepatitis C among children and teenagers enrolled at daycare facilities, kindergartens and municipal elementary education network in the city of Santos, São Paulo, Brazil. Methods: A cross-sectional study was carried out from June 28 to December 14, 2007, in which 4,680 finger-prick blood samples were collected from children and teenagers. A survey questionnaire was applied to their family members. The sample was dimensioned using the software Epi Info version 6 with expected frequency of 1%, acceptable error of 0.5% and confidence interval of 95%. The serological tests were performed using the ELISA technique. The molecular analysis was performed using the technique of polymerase chain reaction in House. Results: Age of the studied population ranged from 7 months to 18 years and 1 month. The general prevalence of anti-HBc reagent was 0.1%, HBsAg was 0.02% and anti-HCV was 0.02%. Conclusions: In children, the general prevalence of serological markers for hepatitis B and C in the city of Santos was low when compared with literature data.